+0  
 
+1
379
4
avatar

7(3^(x+1)) = 2 + 3 / 3^x 

 

In the form a - log(b, 3) where a and b are natural numbers. 

 

The answer is 1 - log(7,3)

 

Which I found by trial and error

Guest Nov 26, 2017
edited by Guest  Nov 26, 2017

Best Answer 

 #4
avatar+7025 
+1

\(7\cdot 3^{x+1} = 2+\dfrac{3}{3^{x}}\\ 21\cdot 3^{2x}-2\cdot 3^x - 3=0\\ \boxed{u=3^x}\\ 21u^2 - 2u -3 = 0\\ (3u+1)(7u-3)=0\\ u = \dfrac{-1}{3}(rej.) \quad OR\quad u = \dfrac{3}{7}\\ 3^{x-1} = \dfrac{1}{7}\\ (x-1) = \log_3\dfrac{1}{7}\\ x = 1 + \log_3(7^{-1})\\ x = 1 - \log_3(7)\)

MaxWong  Nov 27, 2017
 #1
avatar
+1

Solve for x :
7 3^(x + 1) = 3^(1 - x) + 2

 

Multiply both sides by 3^(x - 1):
7 3^(2 x) = 2 3^(x - 1) + 1

 

Subtract 2 3^(x - 1) + 1 from both sides:
-1 - 2 3^(x - 1) + 7 3^(2 x) = 0

 

The left hand side factors into a product with three terms:
1/3 (7 3^x - 3) (3^(x + 1) + 1) = 0

 

Multiply both sides by 3:
(7 3^x - 3) (3^(x + 1) + 1) = 0

 

Split into two equations:
7 3^x - 3 = 0 or 3^(x + 1) + 1 = 0

 

Add 3 to both sides:
7 3^x = 3 or 3^(x + 1) + 1 = 0

 

Divide both sides by 7:
3^x = 3/7 or 3^(x + 1) + 1 = 0

 

Take the logarithm base 3 of both sides:
x = -(log(7/3))/(log(3)) or 3^(x + 1) + 1 = 0

 

Subtract 1 from both sides:
x = -(log(7/3))/(log(3)) or 3^(x + 1) = -1

3^(x + 1) = -1 has no solution since for all z element R, 3^z>0 and -1<0:
x = -(log(7/3))/(log(3))

Guest Nov 26, 2017
edited by Guest  Nov 26, 2017
 #2
avatar
+1

I greatly appreciate your answer, but the answer must be in the form a - log(b, 3). 

 

Where a and b are natural whole Numbers. 

 

I’ve found that a = 1 and b = 7 by trial and error. 

Guest Nov 26, 2017
 #3
avatar
+1

This answer of: x = -(log(7/3))/(log(3))  is the same as:

1 - log(base3), 7 = -0.771243749, which the correct value of x, but not: 1 - log(base7), 3 =0.43542496, which is NOT correct value of x.

Guest Nov 26, 2017
 #4
avatar+7025 
+1
Best Answer

\(7\cdot 3^{x+1} = 2+\dfrac{3}{3^{x}}\\ 21\cdot 3^{2x}-2\cdot 3^x - 3=0\\ \boxed{u=3^x}\\ 21u^2 - 2u -3 = 0\\ (3u+1)(7u-3)=0\\ u = \dfrac{-1}{3}(rej.) \quad OR\quad u = \dfrac{3}{7}\\ 3^{x-1} = \dfrac{1}{7}\\ (x-1) = \log_3\dfrac{1}{7}\\ x = 1 + \log_3(7^{-1})\\ x = 1 - \log_3(7)\)

MaxWong  Nov 27, 2017

10 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.